The economics of climate change - Owen, Anthony David; Hanley, Nick (Routledge, 2004)
With contributions from distinguished authors and covering everything you need to know about global warming and its financial implications, this readable book will appeal across the political and scientific spectrum.
Keywords: Environmental economics.; Climatic changes -- Economic aspects.; Économie de l'environnement.; Climat -- Changements -- Aspect économique.; TECHNOLOGY & ENGINEERING -- Environmental -- Pollution Control.; Climatic changes -- Economic aspects; Environmental economics; Klimatförändringar -- ekonomiska aspekter.; Miljöekonomi.